"\\frac {dx}{(b-c\/a)yz}=\\frac {dy}{(c-a\/b)xz}=\\frac {dz}{(a-b\/c)xy} \\implies""\\frac {xdx+ydy+zdz}{xyz(b-c\/a+c-a\/b+a-b\/c)}=\\frac {dx}{(b-c\/a)yz}"
"\\frac {x^2+y^2+z^2}{b-c\/a+c-a\/b+a-b\/c}=\\frac {x^2}{b-c\/a}+C_1"
"\\frac {xdx+ydy+zdz}{xyz(b-c\/a+c-a\/b+a-b\/c)}=\\frac {dy}{(c-a\/b)xz}"
"\\frac {x^2+y^2+z^2}{b-c\/a+c-a\/b+a-b\/c}=\\frac {y^2}{c-a\/b}+C_2"
"\\frac {xdx+ydy+zdz}{xyz(b-c\/a+c-a\/b+a-b\/c)}=\\frac {dz}{(a-b\/c)xy}"
"\\frac {x^2+y^2+z^2}{b-c\/a+c-a\/b+a-b\/c}=\\frac {z^2}{a-b\/c}+C_3"
Comments
Leave a comment